(3CUhd GdJQhjL h ChbGJ GdaQGZ (B:s (3eONd GdYdhe GdGfSGfjI (B/s - (3OQhjT,ceGd ,GdNhdj,CeHf s ((3GdbGgQI (B:s (3OGQ GdacQ GdYQHj ,s, 1990)
(3jYHQ eaghe GdJQhjL Yf GdhLg GdeTQb ddMjGI h dCf hbJ GdaQGZ dOi GdEfSGf jeKd YeQg aef GdOjQ HfG Cf fgJe HGdJQhjL hHChbGJ GdaQGZ EgJeGefG HhbJ GdYed GdYed h GdGfJGL HGYJHGQ Cf cdG Gdeaghejf eJdGRejf ddhLhO GdGfSGfj hgPG GdcJGH jJfGhd gPG GdeYfi ef NdGd eYGdLI acQjI TGedI JJHfi eONd GdYdhe GdGfSGfjI GdeQJHWI HdQhjL hhbJ GdaQGZ h gj bVjI Jge cd GdeTJZdjf aj eLGd GdEfSGfjGJ HTcd NGU ceG Jge GdEfSGf GdeYGUQ HTcd YGe (B.s
Keywords: (3GdYdhe GdGfSGfjI s